Sleep disorders reveal distress among children and adolescents during the Covid-19 first wave: results of a large web-based Italian survey - Arianna Dondi; Anna Fetta; Jacopo Lenzi; Francesca Morigi; Egidio Candela; Alessandro Rocca; Duccio Maria Cordelli; Marcello Lanari (BMC, 2021)
Abstract Background Measures to contain the Covid-19 pandemic led to significant lifestyle changes for children and adolescents mainly related to the closure of schools and recreational activities, reduced social interaction, and increased family concerns. Methods A cross-sectional online survey of 78 questions investigating social determinants of health, mood changes, symptoms of anxiety, increase in sleep disorders and unusual repetitive movements was offered to parents living in Italy with children ≤18 years; including families of children with disabilities, autism spectrum disorders, chronic diseases, and specific learning disabilities. The survey was conducted on the Qualtrics platform 6 months after the beginning of the pandemic and distributed in hospitals and paediatricians' waiting rooms as well as through social networks. The primary outcomes were the increase in sleep disorders among children and adolescents. Possible risk factors were investigated through multivariable regression. Results Six thousand two hundred ten volunteer parents responded to the questions concerning mood changes, sleep disorders and unusual repetitive movements, and were included in the present study. The majority were female (91.8%) and Italian (97.0%). 72.7% answered that their children had become more nervous, worried, or sad (80.2% in children with learning disabilities); 77.6% reported feelings of loneliness and 69.3% more difficulties in children falling asleep, 30.2% in staying asleep, and 18.7% an increase in nightmares and/or sleep terrors. Statistical analysis identified socioeconomic status, parent's job loss, food insecurity, family attitude toward the pandemic, and children's mood swing, feelings of loneliness, or missing outdoor activities, as major risk factors for sleep disorders. Conclusion The first Covid-19 lockdown impacted children's and adolescents' health through an increase in sleep disorders. In the following phases of the pandemic, this evidence may be useful to investigate and treat these disorders as well as make decisions about containment health policies concerning this age group.